Analisa Pengecekan Peralatan Arrester Menggunakan Thermovisi pada Bay Indarung 1 Gardu Induk Pauh Limo - Andari, Rafika; Amalia, Sitti; Azhari, Ezi (Majalah Ilmiah Teknologi Elektro; Vol 19 No 1 (2020): (Januari - Juni ) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2020.v19i01.P15, 2020)
The hot points that occur in the switchyard are caused by currents flowing in the conductor due to obstacles. The frequent heating part is the terminal and connection portion of the switchyard, especially between the two different metals, as well as the cross section of the conductor that shrinks due to corrosion. So that the part should be considered, by controlling or checking the temperature using Thermovisi. The hot temperature of equipment Arrester in Bay Indarung 1 Pauh Limo is still under normal conditions where the temperature ranges from 20 o C-43 o C. But need attention to the improvement plan. Temperature difference between the phase of Arrester equipment in switchyard of Bay  Indarung 1 Pauh Limo one reaches the III condition, there are conditions I and II where it shows necessary investigation and improvement plan, to avoid occurrence short-circuited between phases (R, S, T).